Low-Cost “Telesimulation” Training Improves Real Patient Pediatric Shock Outcomes in India - James, Ebor Jacob G.; Vyasam, Siva; Venkatachalam, Shakthi; Sanseau, Elizabeth; Cassidy, Kyle; Ramachandra, Geethanjali; Rebekah, Grace; Adhikari, Debasis D.; Deutsch, Ellen; Nishisaki, Akira; Nadkarni, Vinay M. (Frontiers in Pediatrics, 2022)
Introduction Pediatric shock, especially septic shock, is a significant healthcare burden in low-income countries. Early recognition and management of shock in children improves patient outcome. Simulation-based education (SBE) for shock recognition and prompt management prepares interdisciplinary pediatric emergency teams in crisis management. COVID-19 pandemic restrictions on in-person simulation led us to the development of telesimulation for shock. We hypothesized that telesimulation training would improve pediatric shock recognition, process of care, and patient outcomes in both simulated and real patient settings. Materials and Methods We conducted a prospective quasi-experimental interrupted time series cohort study over 9 months. We conducted 40 telesimulation sessions for 76 participants in teams of 3 or 4, utilizing the video telecommunication platform (Zoom©). Trained observers recorded time-critical interventions on real patients for the pediatric emergency teams composed of residents, fellows, and nurses. Data were collected on 332 pediatric patients in shock (72% of whom were in septic shock) before, during, and after the intervention. The data included the first hour time-critical intervention checklist, patient hemodynamic status at the end of the first hour, time for the resolution of shock, and team leadership skills in the emergency room. Results There was a significant improvement in the percent completion of tasks by the pediatric emergency team in simulated scenarios (69% in scenario 1 vs. 93% in scenario 2; p < 0.001). In real patients, completion of tasks as per time-critical steps reached 100% during and after intervention compared to the pre-intervention phase (87.5%), p < 0.05. There was a significant improvement in the first hour hemodynamic parameters of shock patients: pre (71%), during (79%), and post (87%) intervention (p < 0.007 pre vs. post). Shock reversal time reduced from 24 h pre-intervention to 6 h intervention and to 4.5 h post intervention (p < 0.002). There was also a significant improvement in leadership performance assessed by modified Concise Assessment of Leader Management (CALM) instrument during the simulated (p < 0.001) and real patient care in post intervention (p < 0.05). Conclusion Telesimulation training is feasible and improved the process of care, time-critical interventions, leadership in both simulated and real patients and resolution of shock in real patients. To the best of our knowledge, this is one of the first studies where telesimulation has shown improvement in real patient outcomes.